A parametric study on IBR sheeting supported by purlins - Mlasi, Marope Stella (My University, 2016)
This dissertation presents a parametric study conducted on the dimensions of an inverted box rib (IBR) sheet. The objectives of the study were (i) to obtain the optimum dimensions that would be used to simulate new IBR profiles made from standard sheet input coils whilst meeting the stiffness criterion; and (ii) to perform a cost analysis to determine the most economic simulated profile. The dimensions which were varied in the parametric study were rib-height, rib-width, sheet thickness and the number of pans per 686 mm cover width of a single IBR 686 sheet. Numerical experiments were conducted using the Finite Elements Method and Abaqus/CAE software. The results were compared to the predictions obtained from Euler-Bernoulli beam theory. The outputs from the experiments were the sheet deflection from which stiffness was determined, and eigenvalues from which the profiles’ stability and buckling modes were calculated. This study found that sheet stiffness increased as the rib-height, sheet thickness and number of pans per 686 mm cover width increased. In contrast, the rib-width had little effect on the sheet stiffness. Hence, it was concluded that, for any IBR sheet profile, the rib-width should be kept at approximately 23 mm to avoid using more material in the sheet. The optimum dimensions found were rib-height of 34 mm, rib-width of 23 mm and four pans per 686 mm cover width. The commercially available IBR 686 sheet is made up of four pans and has a rib-height and a rib-width of 37 and 33 mm, respectively. It is manufactured from an input sheet coil of 925 mm. Reducing the rib-height from 37 mm to 34 mm and the rib-width from 33 mm to 23 mm resulted in increasing the cover width by 8 %. The optimum dimensions were further used to simulate profiles made from the 925, 940, 1000, 1175, 1219, 1225, 1250 and 1320 mm standard sheet coils in order to find the most economic IBR profiles that met the stiffness criterion. The 1250 mm coil yielded the most economical IBR profile, which has six 97 mm wide pans, and a 996 mm cover width. This profile resulted in a 10 % cost saving compared with the next closest profile.
A dissertation submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, in fulfilment of the requirements for the degree of Master of Science in Engineering Johannesburg, 2016
Keywords: Structural analysis (Engineering); Roofing; Steel, Structural; Sheet-steel